SLE serum induces altered goblet cell differentiation and leakiness in human intestinal organoids - Hensel, Inga Viktoria; Éliás, Szabolcs; Steinhauer, Michelle Irmgard; Stoll, Bilgenaz; Benfatto, Salvatore; Merkt, Wolfgang; Krienke, Stefan; Lorenz, Hanns-Martin; Haas, Jürgen; Wildemann, Brigitte; Resnik-Docampo, Martin (EMBO molecular medicine, 2024)
Human intestinal epithelial cells are the interface between luminal content and basally residing immune cells. They form a tight monolayer that constantly secretes mucus creating a multilayered protective barrier. Alterations in this barrier can lead to increased permeability which is common in systemic lupus erythematosus (SLE) patients. However, it remains unexplored how the barrier is affected. Here, we present an in vitro model specifically designed to examine the effects of SLE on epithelial cells. We utilize human colon organoids that are stimulated with serum from SLE patients. Combining transcriptomic with functional analyses revealed that SLE serum induced an expression profile marked by a reduction of goblet cell markers and changed mucus composition. In addition, organoids exhibited imbalanced cellular composition along with enhanced permeability, altered mitochondrial function, and an interferon gene signature. Similarly, transcriptomic analysis of SLE colon biopsies revealed a downregulation of secretory markers. Our work uncovers a crucial connection between SLE and intestinal homeostasis that might be promoted in vivo through the blood, offering insights into the causal connection of barrier dysfunction and autoimmune diseases.
Online veröffentlicht: 5. Februar 2024
Gesehen am 21.11.2024